Small Mammals Along SW-Atlantic Marshes: Diversity Correlates with Inland Habitats but Abundance Correlates with Marsh Characteristics - Canepuccia, Alejandro Daniel (2014)
Tidal marshes are narrow wetlands distributed worldwide between the ocean and a variety of inland-habitats. The high diversity of interacting terrestrial habitats may influence terrestrial species composition and abundance in marshes. We investigated if characteristics of small mammal assemblages inhabiting the South-West-Atlantic (SWA) marshes are influenced by marsh characteristics, or if they vary in relation to changes in the inland biogeographic context. Sampling at five-Spartina marshes across the SWA-coast showed that plant cover, richness and height (ANOVA analysis) and small mammal assemblages (PERMANOVA analysis) differed between habitats (marsh or inland) depending on the site. Generalized Linear Models (GLMs) showed that abundance of small mammals in marshes is related to vegetation cover and diversity. However, its richness was related to the richness of small mammal at the inland habitats. In fact, species present in each marsh were also recorded in adjacent inland habitats. Species composition differed among similar marshes surrounded by different landscapes, while those in the same landscape did not. Consequently, regional abundance of small mammals in SWA-marshes is consistent with ecological sorting of abundance ranges along environmental gradients (e.g., plant-cover and richness). In contrast, landscape composition and configuration strongly affect marsh small mammal species assemblages, even if the marsh-habitats are quite similar.